What can make things better for parents when babies need abdominal surgery in their first year of life? A qualitative interview study in the UK. Issue 6 (30th June 2018) - Hinton, Lisa; Locock, Louise; Long, Anna-May; Knight, Marian
Abstract : Objectives: To understand the experiences of parents of infants who required surgery early in life. To identify messages and training needs for the extended clinical teams caring for these families—including paediatric surgeons, neonatologists, nurses, obstetricians, midwives and sonographers. Setting: UK-wide interview study, including England, Wales and Scotland. Participants: In-depth interviews were conducted with 44 parents who had a baby who underwent early abdominal surgery. Conditions included those diagnosed antenatally (eg, exomphalos, gastroschisis, congenital diaphragmatic hernia) or those which were detected postnatally (eg, Hirschsprung's disease, necrotising enterocolitis). Interviews were video and audio recorded and analysed using a modified grounded-theory approach. Results: While some parents reported experiencing excellent communication and felt they were listened to and involved by the care team, this was not always the case. Dealing with large, complex medical and surgical teams could result in conflicting messages, uncertainty and distress. Parents wanted information but also described being overwhelmed and wanting to distance themselves to maintain hope. Information and support from other parents in hospital and online groups were highly valued. Of particular concern was support when going home and caring for their baby after discharge; an open access policy for readmission offered a helpful safety net. Conclusions: Listening to the experience of parents provides rich data to enhance clinical understandings on how to improve information and communication with parents, and ameliorate the deep and lasting distress and anxiety that some parents feel when their infants face early surgery. We suggest that the writings of Bourdieu could have resonance in interpreting the experiences of parents as they enter the world of highly technical neonatal medicine and surgery and the knowledge of the professionals who work in these environments.